2017
DOI: 10.1097/md.0000000000008267
|View full text |Cite
|
Sign up to set email alerts
|

Both plasma and tumor tissue miR-146a high expression correlates with prolonged overall survival of surgical patients with intrahepatic cholangiocarcinoma

Abstract: The purpose of this study was to investigate the association of tumor tissue and plasma miR-146a/b expressions with the clinicopathological properties and overall survival (OS) in surgical patients with intrahepatic cholangiocarcinomas (ICC).Eighty-seven patients with ICC were enrolled. Tumor tissue and plasma sample were collected and miR-146a/b expressions were assessed by quantitative polymerase chain reaction (qPCR). The median follow-up duration was 31 months, and the last follow-up date was January 2017.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…More importantly, emerging evidence indicated that FN expression is highly associated with poor overall survival rates in variety of cancer types such as colorectal and gastric cancer [51,52]. On the other hand, high expression of miR-146a were correlated with prolonged overall survival [53]. Based on our finding, the FN assembly is negative correlation with miR-146a regarding to cancer patients overall survival rates.…”
Section: Discussionsupporting
confidence: 57%
“…More importantly, emerging evidence indicated that FN expression is highly associated with poor overall survival rates in variety of cancer types such as colorectal and gastric cancer [51,52]. On the other hand, high expression of miR-146a were correlated with prolonged overall survival [53]. Based on our finding, the FN assembly is negative correlation with miR-146a regarding to cancer patients overall survival rates.…”
Section: Discussionsupporting
confidence: 57%
“…MicroRNAs (miRs) are small non-coding RNAs ~22 nucleotides in length that are associated with multiple biologic processes including cell proliferation, differentiation and apoptosis (7). Abnormal expression of miRNAs has been widely identified in different diseases (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-590-3p inhibits epithelial-mesenchymal transition in ICC via suppressing Smad interacting protein 1 expression (9). Additionally, several differentially expressed miRNAs have been reported as potential diagnostic biomarkers for patients with ICC; for instance, high miR-146a expression in the plasma and tumor tissues is reportedly associated with prolonged overall survival in surgical patients with ICC (7).…”
Section: Introductionmentioning
confidence: 99%